2018
DOI: 10.1016/j.arteri.2018.06.005
|View full text |Cite
|
Sign up to set email alerts
|

Documento de recomendaciones de la SEA 2018. El estilo de vida en la prevención cardiovascular

Abstract: Lifestyle is a complex concept that includes aspects external to ourselves that can modulate and influence our health. The knowledge of the relationship between lifestyle and cardiovascular risk does not attain the level of evidence achieved with clinical trials with drugs, because clinical studies are scarce and mainly of observational nature, albeit based on large cohorts. Nutritional epidemiology has the added difficulty of being based mostly on subjective dietary recall methods to ascertain nutrient and fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
4
0
25

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 15 publications
(31 citation statements)
references
References 115 publications
2
4
0
25
Order By: Relevance
“…The results from the present study indicate that patients with RA do not perceive the increased risk of CV disease associated with this condition. In keeping with our findings, it was suggested that patients with RA do not seem to be aware of this problem [ 14 ] and often have trouble perceiving their actual CV risk [ 15 , 16 ]. With respect to this, a recent systematic review [ 16 ] identified only six studies that assessed the degree of the perceived risk of CV disease development in patients with RA, comparing it with EULAR SCORE or with classic CV risk factors.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…The results from the present study indicate that patients with RA do not perceive the increased risk of CV disease associated with this condition. In keeping with our findings, it was suggested that patients with RA do not seem to be aware of this problem [ 14 ] and often have trouble perceiving their actual CV risk [ 15 , 16 ]. With respect to this, a recent systematic review [ 16 ] identified only six studies that assessed the degree of the perceived risk of CV disease development in patients with RA, comparing it with EULAR SCORE or with classic CV risk factors.…”
Section: Discussionsupporting
confidence: 87%
“…However, despite the well-known fact that physical activity or a Mediterranean diet reduce the morbidity and mortality of CV disease and the symptoms of RA [ 11 , 12 , 13 ], little is known about the adherence to CV prevention factors in patients with RA. In this regard, some data indicate that it is low in the general population [ 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…En definitiva, el consumo moderado de carne (no superior a 4 raciones por semana) no parece perjudicial para el riesgo cardiovascular, si bien hay que elegir piezas magras, retirando la grasa visible antes de su cocinado (6). Las carnes son fuente importante de proteínas animales, y deben alternarse con el pescado consumiendo una de estas opciones al día.…”
Section: Carnesunclassified
“…Las recomendaciones dietéticas tienen que encaminarse a incrementar el consumo de cereales integrales frente al de refinados (preferible la ingesta de pan y cereales integrales sobre la de pan blanco y cereales refinados). El consumo recomendado de cereales integrales es de unas 4 raciones/día, incluyendo pan en todas las comidas del día, pasta 2-3 veces/semana y arroz 2-3 veces/semana (6).…”
Section: Cerealesunclassified
See 1 more Smart Citation